Typifications and additional taxonomic notes in Brazilian Stachytarpheta (Verbenaceae) - Cardoso, Pedro Henrique; Lima, Lucas Vieira; Dittrich, Vinícius Antonio De Oliveira; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2019)
Many names with typification issues were identified during the preparation of a taxonomic treatment of Stachytarpheta for the Flora do Brasil 2020 project. In this context, 22 lectotypes are designated herein along with nomenclatural notes. Additionally, two new synonyms are proposed and clarification on the taxonomic identity of S. viscidula is presented. Therefore, we contribute to stabilize the nomenclatural and taxonomic framework of the genus for the Brazilian flora.